2016
DOI: 10.1111/jocn.13343
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between guidelines and practice in the management of emerging infectious diseases: a qualitative study of emergency nurses

Abstract: It is important to customise guidelines to the needs of frontline nurses. Maintaining cross-departmental consensus on guideline interpretation and operation is also indicated as an important component for effective guideline implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Working at the emergency departments (EDs), emergency nurses act as the gatekeeper of the healthcare system by identifying suspected and confirmed patients with EID infections through meticulous assessment of reporting criteria such as disease manifestations, contact history, and travel history (Lam, Kwong, Hung, Pang, & Chien, 2019a). Also, the emergency nurses' role in controlling the spread of EIDs by performing and maintaining high-quality infection control measures is imperative (Lam, Kwong, Hung, & Pang, 2016). Moreover, they are often involved in patient logistic arrangements within departments and hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Working at the emergency departments (EDs), emergency nurses act as the gatekeeper of the healthcare system by identifying suspected and confirmed patients with EID infections through meticulous assessment of reporting criteria such as disease manifestations, contact history, and travel history (Lam, Kwong, Hung, Pang, & Chien, 2019a). Also, the emergency nurses' role in controlling the spread of EIDs by performing and maintaining high-quality infection control measures is imperative (Lam, Kwong, Hung, & Pang, 2016). Moreover, they are often involved in patient logistic arrangements within departments and hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to be non-compliant with guidelines and protocols intended to prevent the spread of EIDs, such as adherence to hand hygiene practices (Muller, Carter, Siddiqui, & Larson, 2015) and personal protective equipment (PPE) usage (Baduge, Moss, & Morphet, 2017). Studies have revealed that limitations in time and resources were the major cause of non-compliance with recommended practices (Lam, Kwong, Hung, & Pang, 2016;Muller et al, 2015). Interestingly, it has also been reported that the issue of emergency nurses' non-compliance with guidelines could still occur, regardless of the availability of sufficient resources (Lam & Hung, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding emergency nurses' experiences and perceptions of disease management during epidemic events might help identify and address the barriers to their involvement in EID management. The goal of this study was to identify and explore the contextual factors that inhibited the ability of emergency nurses to perform outbreak-response-related duties according to established protocols (Lam, Kwong, Hung, & Pang, 2016;Muller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty increases the risk of exposure to frontline emergency nurses compared with that of other healthcare professionals during an epidemic event [7]. In addition to the occupational risks associated with EIDs, a well-reported challenge encountered by emergency nurses is adapting to the changes in the existing guidelines and recommendations for addressing a particular EID [8][9][10]. Studies have highlighted that emergency nurses are required to frequently and rapidly adjust their practice in accordance with amendments to infection control guidelines, even if such amendments are subtle and/or implicit [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the occupational risks associated with EIDs, a well-reported challenge encountered by emergency nurses is adapting to the changes in the existing guidelines and recommendations for addressing a particular EID [8][9][10]. Studies have highlighted that emergency nurses are required to frequently and rapidly adjust their practice in accordance with amendments to infection control guidelines, even if such amendments are subtle and/or implicit [8,9]. The literature suggests that the antecedents of these challenges could be consequential to the uncertainty and changes experienced by emergency nurses in the workplace during an outbreak: changes and uncertainty within the work environment thus seem to be major and primary barriers to the emergency nursing practice [10].…”
Section: Introductionmentioning
confidence: 99%